Sejarah Pengelolaan Pendidikan Islam pada Masa Kolonial di Indonesia - Qonita Yuhanidz; Yowanda Naura Basitka; Najwa Kamila (Jurnal Bintang Pendidikan Indonesia, 2026)
This study aims to analyze the history of Islamic education management in Indonesia during the Dutch colonial period, identify colonial policies that restricted Islamic education development, and describe the adaptive and resistant responses of Muslim scholars and educational institutions. The study also aims to explain the roles of pesantren and madrasah as institutions that not only survived but underwent significant transformation due to colonial pressures, and to reveal the historical contribution of colonial-era Islamic education management as a foundation for post-independence Islamic education. Using a qualitative literature review method with sources primarily published between 2021 and 2026, this study finds that colonial pressures through the Teacher Ordinance and Wild Schools Ordinance paradoxically spurred innovations in the form of modern madrasahs integrating religious and general knowledge. Organizations such as Muhammadiyah and Nahdlatul Ulama strengthened this educational transformation, making Islamic education not merely a vehicle for religious learning but an instrument of cultural resistance, national consciousness-building, and evidence of Muslim resilience in facing historical challenges.